2010
DOI: 10.1002/elan.200880002
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Anodes for Hydrogen Fuel Cells based on Covalent Attachment of Ni‐Fe Hydrogenases and Direct Electron Transfer to SAM‐Modified Gold Electrodes

Abstract: Immobilization of hydrogenases onto electrodes is of great interest for developing biofuel cells that use H 2 as a fuel. In this way, hydrogenases replace Pt as electrocatalyst for oxidizing H 2 in the anode. We have developed a method of covalent bonding of Desulfovibrio gigas Ni-Fe hydrogenase and Desulfovibrio vulgaris Hildenborough Ni-Fe-Se hydrogenase to gold electrodes modified with a self assembled monolayer (SAM) of 4-aminothiophenol for measuring high electrocatalytic currents of H 2 -oxidation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 39 publications
(45 reference statements)
4
78
1
1
Order By: Relevance
“…After 80 h of continuous operation, 25% of the initial current was maintained. A clear DET signal confirmed that the immobilization method favors an orientation where the active site of the enzyme faces the electrode surface [143]. Gutierrez-Sanchez et al reported similar higher operational stability for covalent conjunction of M. verucaria BOD to gold electrodes modified by carboxylate-terminated SAM [145].…”
Section: Effect Of Covalent Attachmentmentioning
confidence: 78%
See 1 more Smart Citation
“…After 80 h of continuous operation, 25% of the initial current was maintained. A clear DET signal confirmed that the immobilization method favors an orientation where the active site of the enzyme faces the electrode surface [143]. Gutierrez-Sanchez et al reported similar higher operational stability for covalent conjunction of M. verucaria BOD to gold electrodes modified by carboxylate-terminated SAM [145].…”
Section: Effect Of Covalent Attachmentmentioning
confidence: 78%
“…This strategy was applied to various enzymes immobilized on thiol-based SAMs and allowed to determine the surface chemistry on the electrode able to promote DET. One can cite relevant studies that analyzed the catalytic efficiency of A. aeolicus [NiFe]-Hase [142] on negative, positive, or hydrophobic SAMs on gold, of D. gigas Hase on positive SAM on gold [143], of R. eutropha [NiFe]-Hase on negative SAM on silver [61], of Trametes hirsuta LAC on neutral hydrophobic SAM on gold [144], of Cerrena unicolor C139 LAC positive SAM on gold [107], or of Myrothecium verrucaria BOD on positive or negative SAMs on gold [145] (Figure 7). In the latter paper, electrochemistry was coupled to SPR demonstrating that the switching between DET over MET when adsorption was performed either on negative or positive SAM was effectively linked to a different enzyme orientation and not to different enzyme loading.…”
Section: Electrochemistrymentioning
confidence: 99%
“…In periplasmic O 2 -sensitive [NiFe]-Hases, an anionic patch of amino acid residues, mainly glutamate residues, surrounds the FeS distal cluster. [88,162] A high dipole moment points towards this cluster. [163] This polarity allows a physiological electrostatic recognition with the positive tetrahemic cytochrome c 3 .…”
Section: Chemelectrochem Reviews Wwwchemelectrochemorgmentioning
confidence: 94%
“…It was demonstrated that H 2 oxidation switches from a direct to a mediated process according to the charge of the SAM. [162,193,194,198] Intriguingly, even with a monolayer of properly oriented Hase, no noncatalytic signals could be observed, precluding a calculation of catalytic turnover (only in the case of a [FeFe]-Hase did the coupling between electrochemistry on SAM electrodes and electrochemical scanning tunneling microscopy allow a turnover frequency of 21,000 s À1 for hydrogen production to be calculated). [199] No explanation can as yet be given for such a result.…”
Section: Hydrogenasesmentioning
confidence: 99%
“…þ to H 2 and the oxidation of H 2 to 2H þ , and their electrochemistry has been explored for over 30 years [63][64][65][66].…”
Section: Direct Bioelectrocatalysis Of Metalloenzymesmentioning
confidence: 99%